The differences of Slovenian and Italian daily practices experienced in the first wave of covid-19 pandemic - Saša Pišot; Boštjan Šimunič; Ambra Gentile; Antonino Bianco; Gianluca Lo Coco; Rado Pišot; Patrik Drid; Ivana Milovanović (BMC, 2022)
Abstract Background The COVID-19 pandemic situation with the lockdown of public life caused serious changes in people's everyday practices. The study evaluates the differences between Slovenia and Italy in health-related everyday practices induced by the restrictive measures during first wave of the COVID-19 pandemic. Methods The cross-sectional cohort study examined changes through an online survey conducted in nine European countries from April 15-28, 2020. The survey included questions from a simple activity inventory questionnaire (SIMPAQ), the European Health Interview Survey, and some other questions. To compare difference in changes between European countries we examined Italy with severe and its neighbour country Slovenia with low incidence and victims of COVID-19 epidemic. 956 valid responses from Italy (N = 511; 50% males) and Slovenia (N = 445; 26% males) were investigated. Results During the survey, there was a 4.7-fold higher incidence and 12.1-fold more deaths (per 100,000) in Italy than in Slovenia. Barring periods and measures were similar, the latter more stringent in Italy. We found more changes in Italy than in Slovenia: physical inactivity increased (Italy: + 65% vs. Slovenia: + 21%; p < 0.001), walking time decreased (Italy: -68% vs. Slovenia: -4.4%; p < 0.001); physical work increased by 38% in Slovenia (p < 0.001), and recreation time decreased by 37% in Italy (p < 0.001). Italians reported a decrease in quality of general health, fitness level, psychological well-being, quality of life and care for own health (p < 0.001); Slovenians showed a decline in psychological well-being and quality of life (p < 0.001) but generally had a higher concern for their own health (p = 0.005). In pooled participants, changes in eating habits (meal size and consumption of unhealthy food), age and physical inactivity were positively correlated with increases in body mass, while changes in general well-being and concern for health were negatively correlated. Conclusion The study shows that the negative impact of COVID -19 measures is greater in Italy where the pandemic COVID -19 was more prevalent than in Slovenia with low prevalence. Additional consideration should be given to the negative impact of COVID-19 measures on some health-related lifestyle variables when implementing further measures to mitigate the COVID-19 pandemic.